OPINION MININGFRAMEWORK BERBASISKAN LEKSIKAL - Sherly Christina (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
Opinion Mining and Sentiment Analysis can contribute in improving system performance tomeet the user’s needs. The text that represents the user's opinion may express the emotions oropinions implicitly or explicitly. The words that compose the sentence of opinion can have manydifferent meanings, related to the subject being discussed or the words that compose the sentence.This study, conducted a literature study on several researches that related to opinion mining, anddesigned an opinion mining framework based lexicon.